The Effectiveness of Life Skills Training on Enhancement of Self-Esteem and Marital Satisfaction among Addicts in Treatment Period - R Nooripour; A ZadeMohammadi; M Dastras; M Sargolzai (Drug Control Headquarters, Research and Education Office, 2014)
Objective: This study has been done to determine the impact of life skills training on enhancement of self-esteem and marital satisfaction among addicts in treatment period. Method: The research design was semi experimental pretest-posttest with witness group. For each group 12men addicts in treatment period in Qazvin city were selected by available sampling. Rosenberg self-esteem and Enrich marital satisfaction questionnaires were administered among selected samples. Training workshop was conducted on role playing, questioning and answering which was taught by psychology professors in experimental group. Results: Results showed life skills training improved self-esteem and marital satisfaction of addicts in treatment period. Conclusion: Life skills training have a positive impact on self-esteem and marital satisfaction of individuals especially on addicts in treatment period, also life skills training in the field of smoking prevention enhances individuals' skills (such as self-esteem, marital satisfaction, etc...). Life skills training empower person to actualize his knowledge, attitudes and values, and enable him to have motivation for healthy behavior which this will have significant impact on his relationship with his wife.